Ujaran Kebencian Terhadap Capres-Cawapres Prabowo-Gibran Pada Kolom Komentar Media Sosial Instagram Prabowo - Rinna A. Putri; Rismayani Pelawi; Ruth Febriyanti Br. Simarmata; Frinawaty Lestarina Barus (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research aims to describe and analyze forms of hate speech on one of the social media, Prabowo's Instagram account. This research method uses a qualitative descriptive approach. The data analysis method used is the orthographic matching technique with a writing recorder as the determining tool. The results obtained from this research were that there were several negative comments in the form of hate speech towards the presidential and vice presidential candidate pair Prabowo-Gibran.